Perancangan Bahan Ajar Digital Untuk Mata Pelajaran Komputer Akuntansi di SMK Negeri 1 Tanjungpinang - Hendi Hendi; Julyanti Julyanti (ConCEPt - Conference on Community Engagement Project, 2021)
Since the issues of Ministry of Education and Culture’s Circular Letter Number 4 of 2020 concerning Implementation of Education Policies in the Emergency of the Spread of Corona Virus Disease (Covid-19) in March 2020, which was later strengthened by General Secretary’s Circular Letter Number 15 of 2020 concerning Guidelines for Implementing Learning from Home during the Spread of Corona Virus Disease (Covid-19), schools and campuses have begun to close and carry out the teaching and learning process from their respective homes. Online learning is a learning system without face-to-face directly between teachers and students, but online using the internet network (Asmuni, 2020). The sudden change in the learning system from offline to online certainly makes most teachers need to prepare learning media in the form of digital teaching materials, no exception for the 11th grade computerized accounting subject’s teacher in Vocational High School Number 1 Tanjungpinang. Through this community service program, it is hoped that it can help the teacher in enriching digital teaching materials to support online learning. Digital teaching materials use qualitative data sourced from primary data. Primary data is obtained through interviews with the teacher. Not only through interview techniques, data collection also through content analysis techniques to compare the suitability of outputs with basic competencies prevailing in schools. The design of digital teaching materials was carried out from October to December 2020 resulting in two outputs, modules and videos. Module contains questions for transactions during one accounting cycle, each for service and trading companies. The video is in the form of a tutorial video for solving the module questions that have been made. Recommendations for the next person in designing teaching material is it can provide even more variations, not just modules and videos, and also expand the sources for reference in designing digital teaching material.